Peranan Anggaran Biaya Produksi Sebagai Alat Pengendalian Biaya - zainab ,; Kholifatul Akbariyah; Uswatun Khasanah; Choiri . (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2023)
This study aims to determine the role of the production cost budget as a cost control tool in the Home Industry of Temulawak AA. the approach used in this study is a qualitative approach with descriptive methods. By using descriptive analysis techniques and in collecting data through interviews, documentation, observations and literature. Based on the results of the study, it shows that the Home Industry of Temulawak AA has prepared a good budget and carried out control by setting a control standard of 10% of the comparison between budget and realization. The results of the comparison on the Home Industry of Temulawak AA below 10% can be said that the control of production costs at the Home Industry of Temulawak AA is said to be good. So it can be concluded that in Home Industry Temulawak AA, the production cost budget acts as a cost control tool. Keywords: Budget; Control; Production Cost